2008
DOI: 10.1029/2008gl033793
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic size and shape of the mirror mode structures in the solar wind at 0.72 AU

Abstract: [1] We investigate the structure of mirror modes in the solar wind at 0.72 AU using Venus Express magnetic field measurements. The mirror mode structure is identified as the presence of magnetic depression or magnetic ''holes'' in the solar wind with little or no directional change across them. We determine the characteristic size and shape of these structures by examining their durations as a function of the orientation of the magnetic field to the solar wind flow. The mirror mode structure is best fitted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 12 publications
6
117
0
Order By: Relevance
“…In this case, the storms were observed in the leading edge of a SIR detected on 10 July 2007 at 09:45. When observed in great detail (see subsequent figures), MMSs resemble mirror-mode trains reported in previous works of mirror modes in the solar wind (see for instance, Zhang et al [2008], and references therein). However, there are certain features that, to the naked eye, make them different from ordinary trains.…”
Section: Data and Mirror Mode Identificationmentioning
confidence: 50%
See 1 more Smart Citation
“…In this case, the storms were observed in the leading edge of a SIR detected on 10 July 2007 at 09:45. When observed in great detail (see subsequent figures), MMSs resemble mirror-mode trains reported in previous works of mirror modes in the solar wind (see for instance, Zhang et al [2008], and references therein). However, there are certain features that, to the naked eye, make them different from ordinary trains.…”
Section: Data and Mirror Mode Identificationmentioning
confidence: 50%
“…[8] For the solar wind, magnetic holes have also been observed at various heliocentric distances either as isolated holes or trains of closely-spaced magnetic holes [Winterhalter et al, 1994;Zhang et al, 2008;Russell et al, 2008]. Recently, using STEREO high-resolution magnetic field data, Russell et al [2009] reported several mirror-mode events of small amplitude trains, which included not only holes, but also peaks that persisted for hours and were referred to as "mirror-mode storms".…”
Section: Introductionmentioning
confidence: 99%
“…However, MMs have typically larger amplitudes behind quasi-parallel shocks (Génot et al, 2009b). In addition, while also isolated MMs exist (Winterhalter et al, 1994;Zhang et al, 2008), most MMs in planetary magnetosheaths occur as sequences of peaks or dips, so called MM trains (Tsurutani et al, 2011b).…”
Section: M Ala-lahti Et Al: Mirror Mode Wave Occurrence In Icme-mentioning
confidence: 99%
“…To identify individual MMs, we investigate the minima and maxima in the magnetic field data of the combined intervals that have passed the MVA test by applying methods used by Zhang et al (2008Zhang et al ( , 2009 (B i −B) 3 , and the variance σ = δ 2 . Skewness describes the asymmetry of a distribution and is positive for intervals with peaks and negative for intervals with dips (see e.g., Osmane et al, 2015).…”
Section: Mirror Mode (Mm) Identificationmentioning
confidence: 99%
See 1 more Smart Citation